Do thrifty genes exist? Revisiting uricase. Issue 10 (23rd September 2022) - Johnson, Richard J.; Sánchez‐Lozada, Laura G.; Nakagawa, Takahiko; Rodriguez‐Iturbe, Bernardo; Tolan, Dean; Gaucher, Eric A.; Andrews, Peter; Lanaspa, Miguel A.
Abstract: Sixty years ago, the geneticist James Neel proposed that the epidemics of obesity and diabetes today may have evolutionary roots. Specifically, he suggested that our ancestors may have accumulated mutations during periods of famine that provided a survival advantage at that time. However, the presence of this "thrifty genotype" in today's world, where food is plentiful, would predispose us to obesity and diabetes. The "thrifty gene" hypothesis, attractive to some, has been challenged over the years. The authors have previously postulated that the loss of the uricase gene, resulting in a rise in serum and intracellular uric acid levels, satisfies the criteria of a thrifty genotype mutation. This paper reviews and brings up‐to‐date the evidence supporting the hypothesis and discusses the current arguments that challenge this hypothesis. Although further studies are needed to test the hypothesis, the evidence supporting a loss of uricase as a thrifty gene is substantial and supports a role for evolutionary biology in the pathogenesis of the current obesity and diabetes epidemics.